Preoperative hemogram-related parameters to distinguish renal cell carcinoma from benign kidney masses: HERR score - Türkoğlu, Ali Rıza; Üstündağ, Yasemin (The European Research Journal, 2019)
Objectives: Renal cell carcinoma (RCC) accounts for approximately 90% of all kidney malignancies, and it is difficult to preoperatively distinguish between tumors and benign masses without a kidney biopsy in small renal masses. We investigated whether any preoperatively defined hemogram-related parameters had a predictive value that would distinguish RCC from benign kidney masses using a novel scoring method. Methods: Between January 2011 and November 2017, 330 patients diagnosed with kidney masses and who received an operation were included. Fifty-six masses were benign. The neutrophil-to-lymphocyte count (NLR), platelet-to-lymphocyte count, lymphocyte-to-monocyte count, mean platelet volume, platelet count ratio, and hemoglobin to red cell distribution width ratios were calculated. The hemogram-related parameters were combined with the tumor size to establish the hemogram-related risk (HERR) score. The area under the receiver operating characteristics curve, sensitivity, specificity, and likelihood ratios were evaluated to preoperatively diagnose RCC. Results: Histological findings confirmed RCC in 274 patients. The NLR [median (interquartile range)] was higher in patients with RCC, 3.7 (4.7), compared to a benign kidney mass, 2.4 (2.2) (p < 0.001). A HERR score cut-off of ≥ 3 showed a good sensitivity at 78% with an LR+ of 10.8 [95% confidence interval (CI): 7.0-16.4] and an LR- of 1.2 (95% CI: 1.0-1.5). Conclusion: Our study, despite being a preliminary validation, is the first to evaluate hemogram-related parameters for preoperatively discriminating between RCC and benign renal masses, and the HERR score serves as a potential diagnostic biomarker for this.